Retinal biomarkers of Alzheimer’s disease: insights from transgenic mouse models - Bernardes, Rui (2018)
In this paper, we use the retina as a window into the central nervous system and in particular to assess changes in the retinal tissue associated with the Alzheimer’s disease. We imaged the retina of wild-type (WT) and transgenic mouse model (TMM) of Alzheimer’s disease with optical coherence tomography and classify retinas into the WT and TMM groups using support vector machines with the radial basis function kernel. Predictions reached an accuracy over 80% at the age of 4 months and over 90% at the age of 8 months. Texture analysis of computed fundus reference images suggests a more heterogeneous organization of the retina in transgenic mice at the age of 8 months in comparison to controls.